Effects of Helicobacter pylori on the cadherin–catenin complex. Issue 12 (5th May 2006) - Bebb, J R; Leach, L; Zaitoun, A; Hand, N; Letley, D P; Thomas, R; Atherton, J C
Abstract : Background: The cadherin–catenin complex is the key component of the adherens junction in epithelial cells, and changes in this complex are implicated in gastric adenocarcinoma. Germline mutations in E-cadherin have been described in diffuse-type gastric adenocarcinoma. Helicobacter pylori infection is the first stage in gastric carcinogenesis. Aims: To determine whether H pylori was associated with changes in the complex, and whether this was affected by virulence of the strain. Methods: Epithelial cell lines were cultured with H pylori using the wild-type pathogenic and non-pathogenic strains and CagE null and VacA null isogenic mutants. Gastric biopsy specimens at endoscopy were obtained from patients with (n = 17) and without (n = 15) H pylori infection, and E-cadherin and β–catenin expression was assessed by immunohistochemistry. H pylori was typed by polymerase chain reaction from these patients for CagE and VacA . Results: In vitro studies showed that coculture with a pathogenic strain of H pylori led to disruption of epithelial junctional β-catenin expression, but without evidence of nuclear translocation or signalling. This effect was independent of a functional Cag pathogenicity island and vacuolating activity, but dependent on live bacteria. No marked differences in β-catenin or E-cadherin expression were seen in gastric biopsy specimens in patients with and without H pylori infection. Conclusion: Acute H pylori infection disrupts junctional β-catenin in vitro, but chronic infection by H pylori has no effect on E-cadherin and β-catenin expression, as seen in gastric biopsy specimens at the initial gastritis stage of the proposed Correa pathway of gastric carcinogenesis. A later effect at the later stages of atrophy or intestinal metaplasia cannot be ruled out.